A comprehensive pond management study at the Max McGraw Wildlife Foundation - Moe, John L. (My University, 1970)
Fish populations composed of various centrarchids, percids, catostomids, and cyprinids were studied in artificial ponds in northeastern Illinois. Population estimates were performed utilizing the Schumaker-Schnable method. Total length, weight, and sexual maturity were recorded for each fish captured and released. Scale samples were collected from all species. On the basis of length versus year class, data indicated varying degrees of stunting in all ponds.
Keywords: Max McGraw Wildlife Foundation; Ponds -- Management